1984
DOI: 10.1016/0014-5793(84)80846-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium reconstitutes high rates of oxygen evolution in polypeptide depleted Photosystem II preparations

Abstract: Exposure of highly resolved Photosystem II preparations to 2 M NaCl produces an 8OYo inhibition of oxygen-evolution activity concomitant with extensive loss of two water-soluble polypeptides (23 and 17 kDa). Addition of Ca'+ to salt-washed PS II membranes causes an acceleration in the decay of Zt, the primary donor to P-680+, and we show here that this acceleration is due to reconstitution of oxygenevolution activity by Ca'+. Other cations (Mg'+, Mn2+, Sr'+) are much less effective in restoring oxygen evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
276
1
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 380 publications
(297 citation statements)
references
References 8 publications
18
276
1
2
Order By: Relevance
“…First, in the absence of Ca 2+ , PsbP increases the threshold temperature for the S 1 to S 2 transition from 200 K to 250 K (Ono and Inoue 1990a;Ono et al 1992). Second, after addition of Ca 2+ , the presence of the extrinsic polypeptides accelerates restoration of the native conformation of the binding site (as evidenced by recovery of EGTA-insensitive O 2 evolution activity), from hours to minutes (Ghanotakis et al 1984a;Miyao and Murata 1986;Ono and Inoue 1988;Ä delroth et al 1995).…”
Section: Ca 2+ Depletion Methods Revisitedmentioning
confidence: 99%
See 4 more Smart Citations
“…First, in the absence of Ca 2+ , PsbP increases the threshold temperature for the S 1 to S 2 transition from 200 K to 250 K (Ono and Inoue 1990a;Ono et al 1992). Second, after addition of Ca 2+ , the presence of the extrinsic polypeptides accelerates restoration of the native conformation of the binding site (as evidenced by recovery of EGTA-insensitive O 2 evolution activity), from hours to minutes (Ghanotakis et al 1984a;Miyao and Murata 1986;Ono and Inoue 1988;Ä delroth et al 1995).…”
Section: Ca 2+ Depletion Methods Revisitedmentioning
confidence: 99%
“…The highest extent of activity reconstitution is produced by Ca 2+ addition to these samples. It is generally agreed that among all other metals tested, only Sr 2+ is capable of reconstituting O 2 evolution activity, but at lower rates (Ghanotakis et al 1984a;Boussac and Rutherford 1988b). Lockett et al (1990) reported that VO 2+ could also replace Ca 2+ in restoration of O 2 evolution activity and formation of the S 2 multiline signal.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations